What is an appropriate initial diagnostic workup for primary amenorrhea?. Issue 7 (July 2016) - Moody, Bryce; Haynes, James
Abstract : Evidence‐based answer : The initial evaluation should start with a history, including sexual development, accompanied by a physical examination including assessment of secondary sexual characteristics and genital examination. Initial laboratory studies should include urine pregnancy test, folliclestimulating hormone (FSH), prolactin, and thyroid‐stimulating hormone (TSH). The presence or absence of breast development and FSH levels can guide further evaluation (SOR: C, expert consensus based on guideline and case series).